2018
DOI: 10.1039/c8py00074c
|View full text |Cite
|
Sign up to set email alerts
|

The anionic ring-opening polymerization ofN-(methanesulfonyl)azetidine

Abstract: The first anionic ring-opening polymerization of an activated azetidine is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…The synthesis of higher molecular weight PPI polymers was initially reported via cationic ring opening polymerization, , while the polymerization of functionalized azetidine derivatives has been more well-studied. Previously, we investigated the effects of synthesis conditions such as reaction time, temperature, and monomer to perchloric acid initiator ratio on molecular weight, polydispersity, and degree of branching of the obtained PPI; the efficacy of various neutralization techniques was also examined . The PPI-based adsorbents were demonstrated to be promising materials for further development and elaboration for CO 2 capture; however, their stability after oxygen exposure and the effects of varying the acid initiator on polymer structure and performance has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of higher molecular weight PPI polymers was initially reported via cationic ring opening polymerization, , while the polymerization of functionalized azetidine derivatives has been more well-studied. Previously, we investigated the effects of synthesis conditions such as reaction time, temperature, and monomer to perchloric acid initiator ratio on molecular weight, polydispersity, and degree of branching of the obtained PPI; the efficacy of various neutralization techniques was also examined . The PPI-based adsorbents were demonstrated to be promising materials for further development and elaboration for CO 2 capture; however, their stability after oxygen exposure and the effects of varying the acid initiator on polymer structure and performance has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Ring‐opening polymerization (ROP) is a chain‐growth polymerization technique that has been widely applied in the production of numerous commercially important polymeric materials, such as polycaprolactam (Nylon 6), [30] polyethylene oxide (PEO), [31] and polycaprolactone (PCL) [32] . ROP can proceed via a variety of mechanisms, including anionic (AROP), [33] cationic (CROP), [34] radical, [35] and transition metal catalyzed polymerizations, including ring‐opening metathesis polymerizations (ROMP) [14] . In most ROPs, it is the release of ring strain that comprises the ΔH of polymerization and is the driving force for the polymerization [15] .…”
Section: Resultsmentioning
confidence: 99%
“…Reisman et al 142 reported the first example of AROP of an azetidine monomer, N-(methanesulfonyl)azetidine (MsAzet) As evidenced by H-D exchange experiments, this chain transfer occurs through the deprotonation of methanesulfonyl groups of the polymer backbone and the monomer to form sulfamoyl methanide anions. Evidence of minimal chain transfer to DMSO that occurs through the formation of dimsyl anions was also found.…”
Section: Anionic Polymerization Of Azetidinesmentioning
confidence: 99%
“…Anionic ring-opening polymerization of N-(methanesulfonyl)azetidine 142. Scheme 19 Polymerization of TsAzet monomers to produce insoluble homooligomers and a soluble copolymer 159.…”
mentioning
confidence: 99%